A total evidence phylogeny for the processionary moths of the genus Thaumetopoea (Lepidoptera: Notodontidae: Thaumetopoeinae). (16th December 2016) - Basso, Andrea; Negrisolo, Enrico; Zilli, Alberto; Battisti, Andrea; Cerretti, Pierfilippo
Abstract: Processionary moths belong to a group of about 100 species well known for their social behaviour and their urticating systems. The genus Thaumetopoea s.l . includes about 15 species and has been divided into three genera ( Helianthocampa, Thaumetopoea s.s ., and Traumatocampa ) in the last revision, based on key morphological features of the adults and on the host plants of the larvae. We performed a total evidence approach to resolve the phylogeny of the genus Thaumetopoea s.l ., analysing all valid taxa included in this group, plus a broad array of close relatives. Thaumetopoea was monophyletic and supported by several apomorphies. Further subclades corroborated by synapomorphies were identified. Our phylogeny suggests that Thaumetopoea must be regarded as a single genus. The mapping of key life history traits on the total evidence tree allowed us to sketch a plausible identikit of the Thaumetopoea ancestor and to track the evolution of the genus. The ancestor originated in the eastern Mediterranean area, and used broadleaved host plants. Subsequently, a switch to conifers occurred, just once, in a large subclade. The ancestor pupated in the soil, like several current species, but in a few taxa this trait was lost, together with the related morphological adaptations.